The Eu's common security and defence policy in the case of the Eulex mission in Kosovo - Kastrati, Bilbil (Teorija in praksa, 2021)
The article considers whether the EU's CSDP missions are a suitable crisis management mechanism for post-conflict situations, along with the EU's relevance in crisis management at all. For this purpose, the EU's biggest CSDP civilian mission EULEX was chosen as a research case study. The research results reveal that EULEX has not implemented its mandate, not met the expectations of security consumers, not made any difference on the ground, and cannot be seen as an example the EU should rely on in its future missions. Further, EULEX shows that CSDP missions suffer from many shortfalls and the EU CFSP from a capability-expectations gap. The article concludes that the EULEX mission does not show the EU's relevance in the crisis management of post-conflict situations
Keywords: common defence policy; Defence; EU; EULEX; European integration; European integration reforms; European security; Evropska unija; Evropska varnost; krizno upravljanje; Obramba; skupna obrambna politika; SVOP; SZVP